Design Of Reinforced Concrete Slender Columns In a 3-Story Residential Building - Wahyu N, Angga Fandam; Baehaki, Baehaki; Soelarso, Soelarso; Darwis, Zulmahdi (Jurnal Fondasi, 2024)
In some building designs that carry a high aesthetic or architectural value, the use of flat columns brings a number of significant advantages. Their slender design provides more flexibility in interior layout and adds to the aesthetic value of the building. This study was conducted to determine the reinforcement requirements and behavior of flat columns as well as checking the displacement in accordance with SNI 1726:2019. The results show that column I and column L are categorized as swaying and long columns, while column T and column Plus are included in the category of non-swaying and short columns. The required reinforcement requirements are as follows: For column I with dimension 130 x 800, 10D16 main reinforcement is required with D10-100 mm stirrups inside the plastic joint area and D10-150 mm outside the plastic joint area. Column L of dimension 130 x 500 requires 16D16 main reinforcement with D10-100 mm stirrups both inside and outside the plastic joint area. T columns of dimension 130 x 500 require 10D16 main reinforcement with D10-100 mm stirrups inside and outside the plastic joint area. Plus columns of dimension 130 x 400 require 12D16 main reinforcement with D10-100 mm stirrups inside and outside the plastic joint area. The maximum defelction that occurs is still within the permissible tolerance limits of 15.32 mm in the X direction and 11.15 mm in the Y direction so that the building structure is declared safe and stable against the loads received in accordance with SNI 1726: 2019.